Analytic methods in systems and software testing - Kenett, Ron; Ruggeri, Fabrizio; Faltin, Frederick W. (John Wiley & Sons, Inc., 2018)
A comprehensive treatment of systems and software testing using state of the art methods and tools, this book uses numerous examples to provide an understanding in applying these methods to real-world problems. - Resumé vydavatel
Keywords: testování softwaru; software testing; elektronické knihy; sborníky; electronic books; papers of several authors